Role of Probiotics, Prebiotics, and Synbiotics in the Elderly: Insights Into Their Applications - Ale, Elisa C.; Binetti, Ana G. (Frontiers in Microbiology, 2021)
Elderly people are an important part of the global population who suffer from the natural processes of senescence, which lead to changes in the gut microbiota composition. These modifications have a great impact on their quality of life, bringing a general putrefactive and inflammatory status as consequence. Some of the most frequent conditions related to this status are constipation, undernutrition, neurodegenerative diseases, susceptibility to opportunistic pathogens and metabolic disbalance, among others. For these reasons, there is increasing interest in improving their quality of life by non-invasive treatments such as the consumption of probiotics, prebiotics and synbiotics. The aim of the present mini-review is to describe the benefits of these functional supplements/food according to the most recent clinical and pre-clinical studies published during the last decade. In addition, insights into several aspects we consider relevant to improve the quality of future studies are provided.